Research into direct digital method for spectral correlation-interferometric radio direction-finding with double correlation processing - Ципоренко, В.В. (Radiotekhnika, 2012)
The analytical estimations of direction finding assessment error dispersion are got for the conditions of large and small signal/noise ratio at the entrance of radio channels as a result of the conducted researches into the direct digital method of the spectral correlation-interferometric radio direction-finding with a double correlation processing. The imitation design of the direction finder operation is carried out and its basic exactness characteristics are got. The results of analytical calculations and design agree and confirm the possibility of effective direct correlation-interferometric direction-finding with the use of a large antenna base. Expedience of using the weight function of Blackman “window” at spectral analysis is demonstrated.